A position statement on screening and management of prediabetes in adults in primary care in Australia. (June 2020) - Bell, Kirstine; Shaw, Jonathan E.; Maple-Brown, Louise; Ferris, Wendy; Gray, Susan; Murfet, Giuliana; Flavel, Rebecca; Maynard, Bernie; Ryrie, Hannah; Pritchard, Barry; Freeman, Rachel; Gordon, Brett A.
Abstract: Prediabetes has a high prevalence, with early detection essential to facilitate optimal management to prevent the development of conditions such as type 2 diabetes and cardiovascular disease. Prediabetes can include impaired fasting glucose, impaired glucose tolerance and elevated HbA1c. This position statement outlines the approaches to screening and management of prediabetes in primary care. There is good evidence to implement intensive, structured lifestyle interventions for individuals with impaired glucose tolerance. The evidence for those with impaired fasting glucose or elevated HbA1c is less clear, but individuals should still be provided with generalised healthy lifestyle strategies. A multidisciplinary approach is recommended to implement healthy lifestyle changes through education, nutrition and physical activity. Individuals should aim to lose weight (5–10% of body mass) using realistic and sustainable dietary approaches supported by an accredited practising dietitian, where possible. Physical activity and exercise should be used to facilitate weight maintenance and reduce blood glucose. Moderate-vigorous intensity aerobic exercise and resistance training should be prescribed by an accredited exercise physiologist, where possible. When indicated, pharmacotherapy, metabolic surgery and psychosocial care should be considered, in order to enhance the outcomes associated with lifestyle change. Individuals with prediabetes should generally be evaluated annually for their diabetes status.